Development of Circularity Assessment Indices for Construction Sector: A Critical Review - Bengü Güngör; Rand Askar; Akmaral Agibayeva; Ferhat Karaca; L. Bragança (Springer Nature Switzerland, 2024)
The efficient assessment of circularity in buildings requires a comprehensive consideration of diverse elements such as material selection, design principles, construction methods, operational effectiveness, and end-of-life management. However, the absence of a consistent methodology poses a significant challenge in circularity assessment, as extant evaluation techniques either offer a broad perspective on circularity or concentrate on specific components. The lack of clarity in the variations and ranges of circularity indicators further hampers the ability to thoroughly evaluate a building’s performance, leading to a preference for a qualitative approach. This study aims to overcome the challenges associated with the development of circularity assessment indices by proposing a generic framework for index generation, providing guidance to tool developers and decision-makers in understanding the rationale behind circularity indices within the building environment literature. To achieve this goal, the study conducts a literature review elucidating common methods employed in developing circularity indicators and indices as well as the aggregation methods encompassing both qualitative and quantitative indicators, emphasizing how their weights are determined and utilized in the aggregation process. This critical review offers insights into current practices, identifies challenges, and fosters a deeper understanding of the inherent complexities in circularity assessment. Ultimately, this study contributes to the advancement of methodologies for evaluating and enhancing circularity in building, addressing a vital aspect of sustainable construction practices.
Keywords: Epistemology; Philosophy; type of access: open access